APPLICATION OF NEWTON – RAPHSON METHOD TO ANALYZE THERMAL EFFICIENCY OF GAS TURBINE BEFORE AND AFTER ENGINE REPLACEMENT - Damianus Mario Ricky Fernando; Joko Waluyo; Nugroho Dewayanto (Master in Systems Engineering, 2020)
Gas turbine performance is one of the main concerns in the operating of industrial plants. Thermal efficiency is vital to analyze the performance of the gas turbine. This research purpose is to analyze the gas turbine's thermal efficiency after performed engine replacement in one of the gas industries in Kutai Kartanegara, East Kalimantan, Indonesia. The data was taken during the period from August 2017 to July 2018, while engine replacement was performed in February 2018. The data were processed to develop simulation models expressing the characteristics of the equipment. The simulation models were then solved simultaneously using the Newton – Raphson Method. A beneficial advantage of Newton Raphson is that it enables to handle a massive number of data and provides faster iteration compare to other methods. Based on the simulation results, the thermal efficiency before performed engine replacement was 23.43% with a net power of 18.109 MW and fuel consumption of 1.640 Kg/s. Meanwhile, the development of thermal efficiency after performed engine replacement was 28.24% with a net power of 18.597 MW and fuel consumption of 1.397 Kg/s. This indicates that after performing engine replacement, the thermal efficiency increased by 4.81% and saved fuel by 0.243 Kg/s.